PENINGKATAN HASIL BELAJAR IPAS MELALUI PROJECT BASED LEARNING DENGAN FILOSOFI PENDIDIKAN YANG MEMERDEKAKAN PESERTA DIDIK KELAS IV SDN 01 SUMBERSARI - Dita Hardiana (STKIP Subang, 2023)
Improving science learning outcomes through project based learning with an educational philosophy that liberates students in class IV at Sumbersari 01. This study aims to find out whether the application of the Project Based Learning Approach can improve science learning achievement for students of SDN 1 Sumbersari, Jember Regency. And how can the application of the Project based Learning Approach improve the science learning achievement of grade IV students. Based on this research, it can be concluded that: 1) The application of the Project Based Learning approach can improve the science learning achievement of fourth grade students at SDN 1 Sumbersari. 2) Application of the Project Based Learning Approach that can improve the learning achievement of class IV students in Science Science is by taking steps that are in accordance with the principles of project based learning.